Flowering plants. aquifoliales, boraginales, bruniales, dipsacales, escalloniales, garryales, paracryphiales, solanales (except convolvulaceae), icacinaceae, metteniusaceae, vahliaceae /: aquifoliales, boraginales, bruniales, dipsacales, escalloniales, garryales, paracryphiales, solanales (except convolvulaceae), icacinaceae, metteniusaceae, vahliaceae. Eudicots : (2016) - Unknown
No abstract available